Penerapan Firewall dan Intrusion Detection System pada Jaringan Komputer - Ronal Hadi; Riska Kurniyanto Abdullah; Harry Pribadi Fitrian (Journal of Computer Science and Information Technology, 2026)
Network security has become a critical aspect as organizations increasingly rely on network-based information systems. Firewalls, as the first line of defense, have limitations in detecting complex and dynamic cyber attacks. Therefore, integrating Intrusion Detection Systems (IDS) is widely adopted to enhance network resilience. This study aims to analyze the implementation of firewalls and IDS in improving computer network security based on literature review and implementation studies. The research method employs a descriptive-analytical approach through a systematic literature review and comparative analysis of previous studies. The results indicate that the integration of firewalls and IDS significantly improves attack detection rates, accelerates security response, and reduces the risks of data breaches and service disruptions. IDS technologies such as Snort, OSSEC, and Suricata have proven effective in detecting brute force attacks, malware, and Distributed Denial of Service (DDoS) attacks when combined with firewall systems. This study concludes that the integrated implementation of firewalls and IDS is an effective and relevant strategy for securing modern computer networks.